Female-to-Male (FtM) Transgender People's Experiences in Australia A National Study - Jones, Tiffany (Springer eBooks, 2015)
This Briefs is the first national study on female-to-male (FtM) transgender people's experiences in Australia. It describes an extensive study that fills the current gap in Australian research on the specific experiences and beliefs about transition for contemporary Australian FtM transgender people. Following an overview of current literature on the various aspects of and approaches to transgender issues, this briefs describes in detail the design, participants and findings of the study. The Briefs offers useful statistics and stories related to participants' identities, education, health, sexual and social lives. It ends with recommendations to all those working in the various offices and institutions that FtM transgender people encounter in their everyday life, and represents and invaluable resource for researchers, service providers and gender diverse communities alike.